Proceedings of the Sixteenth European Conference on Computer Systems 2021
DOI: 10.1145/3447786.3456244
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating graph sampling for graph machine learning using GPUs

Abstract: Representation learning algorithms automatically learn the features of data. Several representation learning algorithms for graph data, such as DeepWalk, node2vec, and Graph-SAGE, sample the graph to produce mini-batches that are suitable for training a DNN. However, sampling time can be a significant fraction of training time, and existing systems do not efficiently parallelize sampling.Sampling is an "embarrassingly parallel" problem and may appear to lend itself to GPU acceleration, but the irregularity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…We compared two versions of NextDoor that parallelize sampling by sample and by transit, using several sampling algorithms implemented using NextDoor's API. Transit parallelism has shown to be consistently faster, as shown in [19].…”
Section: Systems For Efficient Samplingmentioning
confidence: 90%
See 3 more Smart Citations
“…We compared two versions of NextDoor that parallelize sampling by sample and by transit, using several sampling algorithms implemented using NextDoor's API. Transit parallelism has shown to be consistently faster, as shown in [19].…”
Section: Systems For Efficient Samplingmentioning
confidence: 90%
“…The computation is irregular and is typically performed using the CPU. In our previous work, we found that graph sampling can take up to 62% of an epoch's time if the host has a single GPU (see Table 2) [19]. This bottleneck is further exacerbated if the CPU is attached to multiple GPUs consuming samples for training.…”
Section: Why Scaling Whole-graph Training Is Difficultmentioning
confidence: 99%
See 2 more Smart Citations
“…The node sampling specifically extracts a set of subgraphs and the corresponding embeddings from the original (undirected) graph datasets before aggregating and transforming the feature vectors, which can significantly reduce data processing pressures and decrease the computing complexity without an accuracy loss [27,33]. Since the sampled graph should also be self-contained, the subgraphs and embeddings should be reindexed and restructured.…”
Section: Graph Dataset Preprocessingmentioning
confidence: 99%